2019
DOI: 10.17509/francisola.v3i2.15750
|View full text |Cite
|
Sign up to set email alerts
|

Effets de la mise en œuvre de la classe inversée à travers Edmodo dans l’apprentissage de la grammaire

Abstract: RÉSUMÉ. La stratégie de classe inversée, comme l’une des stratégies de l’apprentissage hybride, a eu un impact positif sur le changement des méthodes d’enseignement traditionnelles, qui passent généralement du temps en classe, en les combinant de manière virtuelle. Cette étude tente d’étudier les effets de la stratégie de classe inversée en utilisant Edmodo dans l’apprentissage de la grammaire française. L'étude est menée en utilisant la méthode quantitative avec le modèle quasi expérimental. Les participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 7 publications
1
8
0
3
Order By: Relevance
“…In language classes, FL methods have been used to support skills such as listening and speaking (Amiryousefi, 2019) and grammar (Darmawangsa and Racmadhany, 2018). Hung (2015) noted that the students in an English FL class put more effort into their learning process than students in traditional classes.…”
Section: Advantages Of Flipped Learning Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In language classes, FL methods have been used to support skills such as listening and speaking (Amiryousefi, 2019) and grammar (Darmawangsa and Racmadhany, 2018). Hung (2015) noted that the students in an English FL class put more effort into their learning process than students in traditional classes.…”
Section: Advantages Of Flipped Learning Methodologymentioning
confidence: 99%
“…Few studies have been conducted on FL in FFL classes with beginner learners (Zou et al, 2020). Darmawangsa and Racmadhany (2018) studied 34 learners from A1/A2 levels learning grammar at university level. They found that student performances improved through the FL methodology.…”
Section: Advantages Of Flipped Learning Methodologymentioning
confidence: 99%
“…All the studies established in educational science and which deal with motivation in a sociocognitive perspective homologate the fact that a passive pedagogy leads to diminished motivation and consequently to quasi-total annihilation of success-building, encompassing the lack of excellence, performance and discipline, absenteeism, dropping out, and failure above all [3]- [5]. Whereas on the other hand, an active pedagogy which is utilizing diversified methods, nourishes motivation and consequently guarantees effective and meaningful learning [6], [7] which leads to success [8] and achievement of the learner's personal and professional objectives [9]- [11]. Teachers' pedagogical choices can therefore be decisive for students' commitment to their studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, based on the fact that an active pedagogical practice [33] can nourish motivation [6], [7] and consequently lead to success [8] and achievement of personal and professional goals [9]- [11], the situation generated by COVID-19 was a profitable opportunity to innovate in pedagogy, within the HINPHT of Fez, and experiment a new active pedagogy (FC) on the one hand, and assess the impact of this FC on students' motivational dynamics on the other hand.…”
Section: Viau's Motivation Scale: Motivometermentioning
confidence: 99%
“…The use of LMS like Edmodo, Google Classroom, and Schoology can be used in asynchronous distance learning to make it easier for teachers and students to achieve learning goals. However, the learning process through LMS must be supported by interesting and motivating learning materials, such as the use of videos, and make this process work in two directions where students and teachers can interact through discussion or comment sections (Darmawangsa & Racmadhany, 2018).…”
Section: Online Learning Strategymentioning
confidence: 99%